To the issue of development of workingland management projects to improve unproductive lands - Koshel, A.; Kolhanova, I.; Kempa, O.; Stacherzak, A. (Land Management, Cadastre and Land Monitoring, 2023)
Scientific-methodical approaches to the development of working land management projects to improve the condition of unproductive lands are proposed. The state policy of land protection envisages the principle of rational nature management on all categories of land, in the event of land disturbance, it envisages their restoration (earthing, reclamation). However, only a small part of the fertile topsoil is used to improve agricultural land. Excavation is a complex of removal, transportation, and application of a fertile layer of soil and potentially fertile rocks on unproductive lands and disturbed lands for the purpose of their improvement. Landfilling in rural areas, by its very nature, is a nature protection measure that is performed in a complex of land management works, which have an investment character and are aimed at preserving the natural environment and increasing the productivity of agricultural land. In market conditions, the concept of "earthing" has been expanded and includes the removal of fertile soil and potentially fertile rocks during the construction of reservoirs, development of quarries, construction work with the excavation of fertile soil and their application not only to unproductive lands in agricultural enterprises, but also in organization of green industrial zones (for greening the territory of the object), liquidation of the consequences of industrial accidents. In these cases, soils with a certain fertility potential are a commodity that has a market demand and a certain value. The economic effect of measures in the working project of land management must be calculated using the discount method, which takes into account both the outflow of money (investments) and the inflow that occurs due to the increase in land productivity. Key words: grounding, working project of land management, disturbed lands, soil protection, fertile soil layer, low-productivity land, land management documentation, land management, management, land use.